Respiratory protective devices for use against chemical, biological, radiological and nuclear (CBRN) agents. Self-contained open-circuit compressed air breathing apparatus incorporating a hood for escape. Speciﬁcation Part 3.1, (24th August 2020) - British Standards Institution,
No abstract available